(untitled) (CIPEEX, 2025)
Labor Gymnastics (GL) is a series of physical exercises performed in the work environment. Among its goals are the prevention of work-related musculoskeletal injuries, combating occupational diseases such as anxiety and stress, and increasing the functional capabilities of workers (Magalhães et al., 2021). GL improves the physical conditioning of its practitioners, making them more willing to perform daily tasks (Toro et al., 2023). This research aimed to identify whether short-term work activity reduces pain in manual workers in a sugar manufacturing industry. The study was conducted in the city of Carmo do Rio Verde, located in the São Patrício Valley region in Goiás. For data collection, a questionnaire was applied in person to 10 workers aged between 18 and 47 years. The questionnaire was applied before the start of work activities and after three weeks of work. The assessment tool focused especially on measuring pain and the physical well-being of the participants. The data revealed that most workers reported feeling tired and experiencing pain related to physical discomfort and excessive effort. Despite the short period of work activities, results indicated that the workplace gymnastics offered did not bring a significant decrease in the perception of pain among workers. It was concluded that, to achieve relevant results in reducing pain, a longer period of training and more research on the subject is necessary. Participant responses suggest that short-term interventions may not be sufficient to reduce physical discomfort accumulated from manual labor. Future research should consider a longer period of intervention to better assess the impacts on workers’ physical health.